Resilience, health behavior and drug use behavior in college students (European Journal of Child Development, Education and Psychopathology, 2015)
Alcohol and tobacco affect college students, it is the third damage to health and primary addiction in Mexico. It was analyzed the interaction between personal factors and resilience in health behaviors and drug use among university students. Predictive correlational design, with random sampling, was applied to the School of Communication, sample calculated using power analysis (N=145 students). There were four instruments .7000 - .8746 Cronbach's alpha. Inferential statistical analysis. The selected personal factors influence on health behavior (p.050). The resilience was predictor of health behavior and drug use in the Model Health Promotion of Pender. Findings with theoretical contribution to the practice and eventually a nursing intervention on healthy lifestyles as protectors in addiction prevention factors in college students.